Shaking table study of the influence of facing on reinforced soil wall connection loads. Issue 4 (28th August 2020) - Xu, P.; Hatami, K.; Jiang, G.
Abstract : Reinforcement plays an important role in seismic stability and performance of reinforced soil retaining walls, and accurate assessment of reinforcement connection loads is an essential step in internal stability analysis of reinforced soil retaining walls using pseudo-static methods. However, the influence that the choice of wall facing could have on reinforcement connection loads is not adequately addressed in the current pseudo-static methods of analysis. In this study, two shaking table tests were carried out on full-height panel and modular block reinforced soil retaining wall models in order to examine the influence of facing type on the connection loads in the two models. The magnitudes and distributions of measured connection loads in the two models are compared with each other and against predictions from two pseudo-static methods. Results of this study shows that reinforcement connection loads are primarily influenced by the outward inertial force of the facing rather than dynamic earth pressure. Predicted connection loads from the Bathurst and the FHWA method showed better agreements with the measured results on the modular block and full-height panel wall models, respectively.